Modern and intelligent controller for a magnetic bearing system - Samsudin, Sharatul Izah (2006)
A magnetic bearing system is a device that uses electromagnetic forces to support a rotor without mechanical contact. The focus of this project will be on the stability and control of the MBC 500 system test bed constructed by Magnetic Moments Incorporated. The MBC 500 system contains a stainless steel shaft or rotor, which can be levitated using eight horseshoe electromagnets, four at each end of the rotor. A controller, which is able to stabilize the position of the rotor by varying the electromagnet force, f produced by the electromagnets at the end of the shaft, will be designed. For this purpose, the formulation of the mathematical dynamic model of magnetic bearing system is derived initially and it was followed by establishing the state space model of the system. Then, system model is linearized at the equilibrium point using a Taylor Series and the shaft is assumed as a rigid body. In addition, a state feedback controller using a pole placement technique and a fuzzy logic controller as an alternative control strategy are designed. This project will be implemented using MATLAB 6.5